Security and privacy in smart city: a secure e-voting system based on blockchain - Fatima zahrae Chentouf; Said Bouchkaren (Institute of Advanced Engineering and Science, 2023)
In recent years, the internet of things (IoT) growth has brought about many technological changes, including the emergence of the notion of the smart city. The development of a smart city requires the integration of IoT devices and information and communication technologies to improve the quality of lives of citizens in many areas such as health, economy, business, agriculture, and transport. However, with this evolution, many cybersecurity risks and challenges have been raised, so it is necessary to develop these technologies in a protected way to avoid being compromised by attackers. Blockchain, being a new technology based on cryptographic principles, can play an important role in securing smart cities. In this survey, we discussed different applications of blockchain technology in smart cities and also studied how blockchain features (transparency, democracy, decentralization, and security) can help in the improvement of smart city services. This analysis will help us to implement an electronic voting model using a smart contract based on the Ethereum blockchain to highlight how blockchain technology can be implemented in smart cities to promote security.